Qualidade fisiológica e sanitária de sementes de soja, com diferentes níveis de vigor, tratadas com Bacillus amyloliquefaciens - Gasparino, Larissa Ayumi Kuninari (Universidade Federal de São Carlos, 2025)
Soybean (Glycine max (L.) Merrill) is one of the most important legume crops for Brazil, serving as a raw material for various industries, biodiesel production, food, plant production, and as a protein source for animal feed. Over time, new technologies have been developed for soybean cultivation to promote more sustainable production with reduced environmental impact. One notable technology is the use of biological agents in seed treatment, such as the bacterium Bacillus amyloliquefaciens. It is known, however, that the effectiveness of seed treatment can be influenced by the vigor of the seed lot, making this information crucial for optimal application of the technology. Therefore, the objective of this study is to assess the physiological potential and sanitary quality of soybean seeds with different vigor levels treated with Bacillus amyloliquefaciens. Three different concentrations of B. a. will be applied to five seed lots with varying vigor levels. In addition to these treatments, a control group without the microorganism will be included. Following treatment, the physiological quality of the seeds will be evaluated through tests such as germination, tetrazolium, seedling emergence, cold test, seedling length, and seedling dry matter weight. The sanitary quality will be assessed using the Blotter test. The results demonstrated that soybean seeds with higher vigor benefited more significantly from treatment using Bacillus amyloliquefaciens (B.a.) in terms of physiological potential, showing greater emergence and initial development. Lower vigor seed lots also responded positively to the treatment when applied at adjusted doses, highlighting the microorganism's potential across different vigor conditions. The application of B.a. additionally reduced the incidence of pathogens such as Fusarium sp., Macrophomina sp., and Aspergillus sp., improving the sanitary quality of the seeds. Moreover, doubled doses of B.a. stood out with the best results, demonstrating the effectiveness of the biological treatment in improving the physiological and sanitary performance of the seeds.
Physiological and sanitary quality of soybean seeds, with different levels of vigor, treated with Bacillus amyloliquefaciens
Keywords: Physiological potential; Potencial fisiológico; Seed sanity; Sanidade de sementes; Viabilidade; Viability; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA